ChemInform Abstract: 4‐OH‐TEMPO/TCQ/TBN/HCl: A Metal‐Free Catalytic System for Aerobic Oxidation of Alcohols under Mild Conditions. Issue 6 (21st January 2016) - Dong, Yanli; Zhao, Xiaomei; Liu, Renhua
Abstract: The described catalytic system permits the selective aerobic oxidation of a wide range of both primary and secondary alcohols, which may also contain heteroatoms such as N and S or carbon‐carbon double bonds.